Efforts to Enhance the Effectiveness of IPAS Learning by Utilizing Video Learning Media - Erin Yusr; Rusandi; Asyafina Rosyada; Chonlawat Junkrob (Journal of Action Research in Education, 2024)
This article discusses efforts to increase the effectiveness of science and social learning through the use of video learning media at SDN Socah 2. Research was conducted using descriptive qualitative methods and shows that video learning media has a positive impact on some students, but does not have much of an impact on other students. Factors such as learning style, involvement in the learning process, motivation, interests, and learning environment also influence student learning outcomes. The use of video learning media can increase students' interest and understanding of the subject matter. The combination of complex learning strategies, an active teacher role, and attractive video design can increase learning effectiveness. This research provides a potential solution to improve student learning outcomes through the use of video learning media by paying attention to variations in student learning styles and their involvement in the learning process.